2000
DOI: 10.1074/jbc.275.15.11404
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Suppresses Transcription of Lipoprotein Lipase Gene

Abstract: Estrogen exerts a variety of effects not only on female reproductive organs but also on nonreproductive organs, including adipose tissue. Estrogen inhibits obesity triggered by ovariectomy in rodents. We studied the mechanism underlying this estrogen-dependent inhibition of obesity. Estrogen markedly decreased the amounts of fat accumulation and lipoprotein lipase (LPL) mRNA as well as triglyceride accumulation in genetically manipulated 3T3-L1 adipocytes stably expressing the estrogen receptor (ER). A pLPL(19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(60 citation statements)
references
References 50 publications
(56 reference statements)
3
57
0
Order By: Relevance
“…These results are in agreement with observations in animal models of ovariectomy, ER␣ knockout and aromatase-deficient (8,9,11,12) and estrogen-deficient women. (38) KS483 is a fetal mouse calvaria-derived clonal cell line committed to the osteoblast lineage.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are in agreement with observations in animal models of ovariectomy, ER␣ knockout and aromatase-deficient (8,9,11,12) and estrogen-deficient women. (38) KS483 is a fetal mouse calvaria-derived clonal cell line committed to the osteoblast lineage.…”
Section: Discussionsupporting
confidence: 82%
“…(19) Two types of ERs, namely, ER␣ and ER␤, mediate the biological effects of estrogen in target tissues including bone (1,20,21) and adipose tissue. (8,11,12) Both receptors can form heterodimers within the target cells and ER␤ modulates ER␣ transcriptional activity. (22,23) Furthermore, ER␤2, a splice variant of ER␤, can function as a negative regulator of estrogen action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Akt can then phosphorylate substrates such as glycogen synthase kinase-3, 6-phosphofructo-2-kinase, and BAD. More recently, it was found that eNOS is also an Akt substrate and is activated by Akt-dependent phosphorylation to release NO in endothelial cells (31-34).The actions of estrogen can be mediated by the classical nuclear receptors, ER␣ and ER␤ (35,36) or through other putative membrane receptors. By definition, rapid effects of estrogen that involve nongenomic mechanisms are independent of transcriptional activation by the nuclear ERs.…”
mentioning
confidence: 99%
“…The actions of estrogen can be mediated by the classical nuclear receptors, ER␣ and ER␤ (35,36) or through other putative membrane receptors. By definition, rapid effects of estrogen that involve nongenomic mechanisms are independent of transcriptional activation by the nuclear ERs.…”
mentioning
confidence: 99%